A layered material for dynamic photoelastic experiment and a manufacturing method thereof
By preparing layered epoxy resin materials, the problem that traditional photoelastic experimental materials cannot simulate the mechanical characteristics of the layered rock mass interface is solved, and a photoelastic model with high transparency and good mechanical properties is achieved, meeting the needs of layered rock mass research.
Patent Information
- Application Number
- CN202211605790.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-14
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2042-12-14
AI Technical Summary
Traditional photoelastic experimental materials cannot meet the needs of layered rock mass research, especially when simulating the stress, strain state and crack propagation laws at the interface of layered materials.
Using layered epoxy resin material, the corresponding epoxy resin mixed solution ratio is determined by measuring the mechanical parameters of each layer of rock, and a photoelastic model with a good layered interface is prepared by mold casting and constant temperature curing methods.
Laminated materials with high transparency, good mechanical and optical properties can better simulate the layering and interface of actual layered rocks and study their mechanical properties.
Smart Images

Figure CN116200003B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of dynamic photometry experimental research in experimental mechanics, and in particular to a layered epoxy resin dynamic photoelastic material and a preparation method thereof. Background Art
[0002] Layered rock mass is one of the common rock structures. The stress and disturbance in the layered rock mass will not only cause damage and cracking of the rock mass, but also cause the opening and dislocation of the bedding plane or structural plane. Compared with a single rock structure, the propagation law of stress waves in the layered rock mass is quite different. Due to the different properties of the rock layers that constitute the layered rock mass, the interface between the rock layers has a great influence on the distribution of rock cracks. Traditional photoelastic experimental materials can no longer meet the needs of layered rock mass research. Therefore, a photoelastic model with a good layered interface is proposed to study the mechanical characteristics such as stress, strain state and crack propagation law at the interface of layered materials in a photoelastic experimental system. Summary of the invention
[0003] The purpose of the present invention is to provide a layered material and a preparation method for dynamic photoelasticity experiments, which can produce an epoxy resin layered model material with good transparency.
[0004] The specific technical solutions are as follows:
[0005] A method for preparing a layered material for a dynamic photoelastic experiment comprises the following steps:
[0006] a. Measure the mechanical parameters of each layer of rock constituting the layered rock mass, and obtain various physical and mechanical parameters of each layer of rock constituting the layered rock mass;
[0007] b. Determine the raw material ratio of the mixed solution corresponding to each layer according to the measured physical and mechanical parameters of each layer of rock; prepare the mixed solution of each layer in turn according to the determined raw material ratio of the mixed solution, and stir it fully in a water bath at 80°C;
[0008] According to the similarity principle of the model experiment, the ratio of the epoxy resin material mixed solution corresponding to the mechanical parameters of the rock materials of each layer of the actual layered rock mass is determined as follows:
[0009] The ratio of the mixed solution a is epoxy resin E-54 (#616): methyl hexahydrophthalic anhydride: plasticizer dibutyl phthalate: accelerator DMP-30: epoxy resin defoamer = 250:165:0:3:1.
[0010] The ratio of the mixed solution b is epoxy resin E-44 (#6101): methyl hexahydrophthalic anhydride: plasticizer dibutyl phthalate: accelerator DMP-30: epoxy resin defoamer = 250:184:22:3:1.
[0011] The ratio of the mixed solution c is epoxy resin E-51 (#618): methyl hexahydrophthalic anhydride: plasticizer dibutyl phthalate: accelerator DMP-30: epoxy resin defoamer = 250:162:14:3:1.
[0012] The ratio of the mixed solution d is epoxy resin E-44 (#6101): methyl hexahydrophthalic anhydride: plasticizer dibutyl phthalate: accelerator DMP-30: epoxy resin defoamer = 250:173:34:3:1.
[0013] The ratio of the mixed solution e is epoxy resin E-51 (#618): methyl hexahydrophthalic anhydride: plasticizer dibutyl phthalate: accelerator DMP-30: epoxy resin defoamer = 250:200:38:3:1.
[0014] The ratio of the mixed solution f is epoxy resin E-54 (#616): methyl hexahydrophthalic anhydride: plasticizer dibutyl phthalate: accelerator DMP-30: epoxy resin defoamer = 250:205:0:3:1.
[0015] c. Pour the first layer of mixed solution into the mold and perform preliminary curing at a constant temperature; the preliminary curing temperature is 80°C and the temperature is kept constant for 2 hours;
[0016] d. After the initial curing, install a fixture outside the mold, pour the second layer of mixed solution into the mold, and perform initial curing at a constant temperature; the initial curing temperature is 80°C, and the temperature is kept constant for 2 hours;
[0017] e. Repeat steps c and d until each layer of the mixed solution is poured;
[0018] f. After the pouring is completed, the layered epoxy resin material is heated and cured;
[0019] g. After curing, the layered epoxy resin material is annealed.
[0020] The method for making layered materials for dynamic photoelastic experiments, in the step a, mechanical parameters of standard specimens of each rock layer are measured, including uniaxial compression test, shear test, splitting test and strain gauge electrical test, to obtain the mechanical parameters of rock materials of each layer of the layered rock, including elastic modulus, compressive strength, tensile strength, Poisson's ratio, internal friction angle, and cohesion.
[0021] The method for preparing layered materials for dynamic photoelastic experiments, in the step b, the raw materials for preparing the mixed solution include epoxy resin, methyl hexahydrophthalic anhydride, accelerator DMP-30, epoxy resin defoamer, and plasticizer dibutyl phthalate; mechanical parameter tests such as uniaxial compression test, shear test, splitting test and strain gauge electrical test are carried out on epoxy resin standard specimens prepared from mixed solutions with different proportions, and the material mechanical parameter variation law of epoxy resin materials prepared from mixed solutions with different proportions is explored; according to the similarity principle of the model experiment, the proportion value of the epoxy resin material mixed solution corresponding to the mechanical parameters of the rock materials of each layer of the actual layered rock mass is determined, so as to prepare for the later casting of the layered epoxy resin photoelastic material.
[0022] The method for preparing the layered material for dynamic photoelastic experiment, in the step b, the epoxy resin mixed solution ratio is epoxy resin: methyl hexahydrophthalic anhydride: plasticizer dibutyl phthalate: accelerator DMP-30: epoxy resin defoamer = 250:155-205:0-38:3:1.
[0023] The method for preparing a layered material for a dynamic photoelastic experiment, in the step b, firstly prepare a first layer of mixed solution according to a determined ratio, weigh various raw materials required according to the raw material ratio, first pour the epoxy resin into a beaker, then add methyl hexahydrophthalic anhydride, plasticizer dibutyl phthalate, accelerator DMP-30, epoxy resin defoamer in sequence, and stir the mixed solution in an 80°C water bath; the stirring rate is preferably 80-100r / min; manually stir until the solution floating on the surface is evenly mixed with the lower layer, and then continue to stir for 30 minutes in an 80°C water bath using a water bath thermostatic stirrer; the entire stirring process is completed under closed conditions, and the room temperature is not lower than 25°C. During the stirring process, the water vapor generated by the water bath heating on the stirring rod should be wiped off in time to prevent the water vapor from dripping into the mixed solution.
[0024] The method for making a layered material for a dynamic photoelastic experiment, in the step c, the mold is made of double-layer tempered glass, the inner surface of the double-layer tempered glass is evenly sprayed with epoxy resin release agent LP-1309, the double-layer tempered glass is separated by a seal and glued to the left and right lower three edges of the glass with special glue, keeping the spacing between the double-layer glass the same, the seal and the tempered glass are glued with special glue and then clamped with a large clip, left at room temperature for 48 hours or baked in an oven at 80°C for 4 hours until completely set and hardened, and then the large clip on the mold is removed.
[0025] The method for preparing a layered material for a dynamic photoelastic experiment, in the step c, the stirred first layer of the mixed solution is quickly poured along the inner wall of the mold, so that the mixed solution flows down in strands, to avoid bubbles generated during the pouring of the mixed solution that affect the subsequent experimental results; during the pouring process, the mold can be placed horizontally, or a certain angle of inclination can be created; the entire pouring process is guaranteed to be completed within 2 minutes, to avoid the pouring time being too long, resulting in a decrease in the temperature of the mixed solution, resulting in a decrease in its fluidity, and causing the upper liquid surface of the mixed solution in the mold to be uneven.
[0026] The method for making a layered material for a dynamic photoelastic experiment, in the step d, the first layer of the poured mixed solution is initially cured at a constant temperature for 2 hours, at which time it solidifies into a jelly-like state and has no fluidity; the mold is taken out of the oven, 5-6 clamps are clamped on the bottom side of the mold, the clamp spacing is kept equal, the upper fulcrum of the clamp is just at the liquid surface position, and the handle of the clamping rotating screw of the clamp is rotated clockwise until it cannot rotate; the entire clamp installation process should be completed within 5 minutes, and after the installation is completed, the entire mold is immediately placed in a preheated 80°C oven.
[0027] The method for preparing layered materials for dynamic photoelastic experiments, in the step d, prepares a second layer of mixed solution according to the determined raw material ratio of the mixed solution, and the preparation steps are the same as the preparation steps of the first layer of mixed solution; the second layer of mixed solution begins to be stirred 30 minutes before the first layer of mixed solution is initially cured at a constant temperature, so as to ensure that the second layer of mixed solution has been stirred when the special fixture is installed after the initial curing of the first layer of mixed solution.
[0028] In the method for making a layered material for a dynamic photoelastic experiment, in the step d, the stirred second layer of mixed solution is quickly poured into the baked mold along the mold wall, so that the mixed solution flows down in streams, thereby avoiding bubbles generated during the pouring of the mixed solution and affecting the subsequent experimental results; the pouring is stopped when the mixed solution b is poured to the required height, and the subsequent steps repeat the steps of preliminary curing of the first layer of the mixed solution and fixture installation.
[0029] In the method for preparing the layered material for dynamic photoelastic experiment, in the step f, the curing temperature is:
[0030] a. Heating stage:
[0031] ① Within 0.5 hours, the temperature rises from room temperature to 80°C;
[0032] ②Raise the temperature from 80℃ to 120℃, 10℃ per hour;
[0033] b. Constant temperature stage
[0034] ③120℃ constant temperature for 2 hours;
[0035] c. Cooling stage
[0036] ④ Cool down from 120℃ to 80℃, 5℃ per hour;
[0037] ⑤Within 0.5 hours, reduce the temperature from 80℃ to room temperature.
[0038] The method for making a layered material for a dynamic photoelastic experiment, in the step g, after curing is completed, the layered material in the mold is taken out, and it is checked to confirm that there are no obvious scratches on the surface of the layered material, no bubbles inside, and the interface between the layers is flat; the material is processed into a desired shape and size; it is determined that the processed test piece has no obvious defects, and then the test piece is immersed in silicone oil and then placed in an oven for annealing to eliminate residual stress inside the layered material.
[0039] In the method for preparing the layered material for dynamic photoelastic experiment, the temperature set for annealing the layered material is:
[0040] a. Heating stage:
[0041] ①In 4 hours, the temperature rises from room temperature to 150℃;
[0042] b. Constant temperature stage
[0043] ②150℃ constant temperature for 5 hours;
[0044] c. Cooling stage
[0045] ③ Cool down from 150℃ to 120℃, 1℃ per hour;
[0046] ④ Cool down from 120℃ to room temperature, cooling down by 5℃ per hour.
[0047] A layered material for dynamic photoelasticity experiment obtained according to any of the above-mentioned preparation methods.
[0048] The present invention can prepare a layered material for dynamic photoelasticity. The layered model material can better simulate the actual layered rock stratification and interface to study the stress, strain state and crack propagation law of the layered material interface. The layered material has the advantages of high transparency, high elastic modulus, mechanical and optical proportional limits, high optical sensitivity, small initial stress effect, small edge time effect, small mechanical creep and optical creep, isotropy, easy processing and casting, large-scale processing, low material price, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1 Flowchart for the preparation of layered materials for dynamic photoelastic experiments.
[0050] Figure 2 Schematic diagram of heating and stirring the mixed solution in a water bath.
[0051] Figure 3 Schematic diagram of the tempered glass mold with a large fixture installed.
[0052] Figure 4 Schematic diagram of pouring layered materials with a custom fixture for installation.
[0053] Figure 5 Schematic diagram of the special fixture.
[0054] Figure 6 Schematic diagram of curing temperature curve.
[0055] Figure 7 This is a schematic diagram after the layered material is poured.
[0056] Figure 8 Schematic diagram of annealing temperature curve.
[0057] Description of reference numerals:
[0058] 1. Removable stirring rod, 2. Beaker, 3. Water bath temperature display, 4. Constant temperature water bath heater, 5. Stirring rate regulator, 6. Double-layer tempered glass, 7. Large clamp, 8. Mould left and right side seals, 9. Mould bottom side seal, 10. U-shaped rod, 11. Clamping and rotating screw, 12. Layered material interface, 13. Layered interface inclination. DETAILED DESCRIPTION
[0059] The present invention is described in detail below in conjunction with specific embodiments.
[0060] Those skilled in the art should understand that the following specific description is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention.
[0061] Example
[0062] The present invention provides a layered material and a manufacturing method for dynamic photoelasticity experiment, wherein the preferred specific implementation is:
[0063] Reference Figure 1 The purpose of the present invention is to provide a layered dynamic photoelastic material and a preparation method thereof, which can produce an epoxy resin layered model material with good transparency. The specific steps are as follows:
[0064] a. The mechanical parameters of the standard specimens of each rock layer are measured to obtain the mechanical parameters of the rock materials of each layer of the layered rock mass. The main measurement methods are uniaxial compression test, shear test, splitting test and strain gauge electrical test. The measured mechanical parameters of the rock materials of each layer of the layered rock mass include elastic modulus, compressive strength, tensile strength, Poisson's ratio, internal friction angle, and cohesion.
[0065] b. Determine the raw material ratio of the mixed solution for each layer based on the measured physical and mechanical parameters of each layer of rock.
[0066] The standard epoxy resin specimens made from mixed solutions with different proportions were subjected to mechanical parameter tests such as uniaxial compression test, shear test, splitting test and strain gauge electrical test, and the variation law of material mechanical parameters of epoxy resin materials made from mixed solutions with different proportions was explored: with the increase of the mass ratio of epoxy resin to curing agent, the density of epoxy resin material increased, the compressive strength decreased, the elastic modulus increased, the tensile strength decreased, the cohesion decreased, the internal friction angle increased, and the Poisson's ratio decreased. With the increase of the content of plasticizer, the elastic modulus decreased. The parameter range was preliminarily determined, and then fine-tuned according to the actual measured physical and mechanical parameters of the layered rock mass. According to the similarity principle of the model experiment, the ratio of the epoxy resin material mixed solution corresponding to the mechanical parameters of the rock materials of each layer of the actual layered rock mass is determined as follows:
[0067] The ratio of the mixed solution a is epoxy resin E-54 (#616): methyl hexahydrophthalic anhydride: plasticizer dibutyl phthalate: accelerator DMP-30: epoxy resin defoamer = 250:165:0:3:1.
[0068] The ratio of the mixed solution b is epoxy resin E-44 (#6101): methyl hexahydrophthalic anhydride: plasticizer dibutyl phthalate: accelerator DMP-30: epoxy resin defoamer = 250:184:22:3:1.
[0069] The ratio of the mixed solution c is epoxy resin E-51 (#618): methyl hexahydrophthalic anhydride: plasticizer dibutyl phthalate: accelerator DMP-30: epoxy resin defoamer = 250:162:14:3:1.
[0070] The ratio of the mixed solution d is epoxy resin E-44 (#6101): methyl hexahydrophthalic anhydride: plasticizer dibutyl phthalate: accelerator DMP-30: epoxy resin defoamer = 250:173:34:3:1.
[0071] The ratio of the mixed solution e is epoxy resin E-51 (#618): methyl hexahydrophthalic anhydride: plasticizer dibutyl phthalate: accelerator DMP-30: epoxy resin defoamer = 250:200:38:3:1.
[0072] The ratio of the mixed solution f is epoxy resin E-54 (#616): methyl hexahydrophthalic anhydride: plasticizer dibutyl phthalate: accelerator DMP-30: epoxy resin defoamer = 250:205:0:3:1.
[0073] c. Reference Figure 2, first prepare the mixed solution a according to the determined ratio. Set the water bath temperature display 3 to 80°C. At 80°C, the fluidity of the epoxy resin will increase, so stir the mixed solution a under 80°C water bath conditions. Adjust the stirring rate regulator 5, and the stirring rate is preferably 80-100r / min to avoid bubbles due to excessive speed, and the mixed solution is not stirred evenly due to too low speed. Weigh the various raw materials required according to the raw material ratio, first pour 86.39g of epoxy resin E-54 (#616) into beaker 2, then add 57.69g of methyl hexahydrophthalic anhydride, 1.04g of accelerator DMP-30, and 0.34g of epoxy resin defoamer in turn, and stir with a water bath thermostatic stirrer. Then stir manually until the solution floating on the surface is evenly mixed with the lower layer, and then continue to stir with a water bath thermostatic stirrer under 80°C water bath conditions for 30 minutes.
[0074] The entire stirring process is completed in a closed space, and the room temperature is not lower than 25°C. During the stirring process, the water vapor generated by the water bath heating on the stirring rod 1 should be wiped off in time to prevent the water vapor from dripping into the mixed solution. Safety measures should be taken during the stirring process. The methyl hexahydrophthalic anhydride in the raw material is slightly toxic, so a gas mask should be worn.
[0075] Reference Figure 3 The main body of the mold is a double-layer tempered glass 6 with a size of 430mm×370mm, which is high temperature resistant and reusable. The material is transparent and can clearly see whether the interface formed by the two different mixed solutions is uniform and flat.
[0076] The inner surface of the double-layer tempered glass is evenly sprayed with epoxy resin release agent LP-1309, and the double-layer tempered glass is separated by left and right side seals 8 and bottom side seals 9 and glued to the left and right lower three edges of the glass with special glue to keep the distance between the double-layer glass the same. After the special glue is used to glue the seals and the tempered glass, they are clamped with a large clamp 7, left at room temperature for 48 hours or baked in an oven at 80°C for 4 hours until they are completely set and hardened, and then the large clamp 7 on the mold is removed.
[0077] Reference Figure 4 The mold that has been hardened can be used for pouring the mixed solution. Heat the mold in advance, place the mold horizontally, and quickly pour the stirred mixed solution a along the inner wall of the glass plate to make the mixed solution flow down in streams to avoid bubbles during the pouring of the mixed solution that affect the subsequent experimental results. Stop pouring when the pouring liquid level reaches the required height, gently put it into the baking oven, set it to 80℃ and heat it for 2 hours to preliminarily solidify the mixed solution a. The entire pouring process is guaranteed to be completed within 2 minutes to avoid the pouring time being too long, which will cause the temperature of the mixed solution to drop, resulting in a decrease in its fluidity and an uneven upper liquid surface of the mixed solution in the mold.
[0078] d. The poured mixed solution a is initially cured at a constant temperature for 2 hours, at which time it solidifies into a jelly-like state and has no fluidity. Take out the mold from the oven, clamp 5-6 special clamps on the bottom side of the mold, keep the special clamps at equal spacing, and the upper fulcrum of the special clamp just at the liquid surface, and rotate the handle of the clamping and rotating screw 11 of the special clamp clockwise until it cannot rotate. The upper fulcrum of the special clamp refers to the position of the clamping and rotating screw at the top of the special clamp. Clamping at the liquid surface can make the double-layer tempered glass of the mold and the epoxy resin model fit tightly at the liquid surface to prevent the upper mixed solution from entering the gap between the two during the subsequent curing process and generating a large number of tiny bubbles at the interface.
[0079] The entire special fixture installation process should be completed within 5 minutes. After the installation is completed, the entire mold should be quickly placed in a preheated 80°C oven to prevent the epoxy resin model formed by the initial curing of the mixed solution a from shrinking due to a sudden drop in temperature, resulting in the separation of the tempered glass mold and the epoxy resin model, and air entering the gap between the tempered glass mold and the epoxy resin model. Otherwise, when the upper mixed solution is subsequently poured and continues to cure, the air in the gap will affect the flatness of the epoxy resin model surface.
[0080] Reference Figure 5 The special fixture is composed of a U-shaped rod 10 and a clamping and rotating screw 11, which fixes the tempered glass in the U-shaped rod to ensure that the height of the liquid level in the mold is consistent with the height of the fulcrum on the special fixture, so that the double-layer tempered glass of the mold and the epoxy resin model are tightly fitted at the liquid level to prevent the upper mixed solution from entering the gap between the two during the subsequent curing process and generating a large number of tiny bubbles at the interface.
[0081] Prepare the second layer of mixed solution b according to the determined ratio, and prepare the raw materials with corresponding specific gravity: 87.46g epoxy resin E-44 (#6101), 64.43g methylhexahydrophthalic anhydride, 7.73g plasticizer dibutyl phthalate, 0.97g accelerator DMP-30, 0.32g epoxy resin defoamer. The preparation steps are the same as those of mixed solution a.
[0082] The mixed solution b starts to be stirred 30 minutes before the mixed solution a is initially cured at a constant temperature, so as to ensure that the mixed solution b has been stirred when the special fixture is installed after the initial curing of the mixed solution a.
[0083] Pour the stirred mixed solution b quickly along the wall of the glass plate into the baked mold, so that the mixed solution flows down in streams to avoid bubbles during the pouring of the mixed solution that affect the subsequent experimental results. Rotate the mold to the required angle of 10°, and stop pouring when the mixed solution b is poured to the required height. Repeat the subsequent steps of preliminary solidification of the mixed solution a and installation of the special fixture.
[0084] e. Repeat steps c and d until each layer of the mixed solution is poured.
[0085] Raw materials for mixed solution c: 67.94g epoxy resin E-51 (#618), 44.04g methylhexahydrophthalic anhydride, 3.75g plasticizer dibutyl phthalate, 0.81g accelerator DMP-30, 0.27g epoxy resin defoamer. The mold is placed horizontally during pouring.
[0086] Raw materials for mixed solution d: 63.49g epoxy resin E-44 (#6101), 43.93g methylhexahydrophthalic anhydride, 8.67g plasticizer dibutyl phthalate, 0.76g accelerator DMP-30, 0.25g epoxy resin defoamer. The mold is placed horizontally during pouring.
[0087] Raw materials for mixed solution e: 80.54g epoxy resin E-51 (#618), 64.43g methylhexahydrophthalic anhydride, 12.15g plasticizer dibutyl phthalate, 0.97g accelerator DMP-30, 0.32g epoxy resin defoamer. The mold is placed horizontally during pouring.
[0088] Raw materials for mixed solution f: 87.08g epoxy resin E-54 (#616), 72.57g methylhexahydrophthalic anhydride, 1.05g accelerator DMP-30, 0.35g epoxy resin defoamer. The mold is placed horizontally during pouring.
[0089] The heights of the 6 layers of mixed solution from bottom to top are 50 mm, 55 mm, 40 mm, 40 mm, 50 mm, 55 mm, and the angles of the liquid surface are 0°, 10°, 0°, 0°, 0°.
[0090] f. After pouring, the layered epoxy resin material is heated and cured.
[0091] Reference Figure 6 , the temperature of the layered material curing setting is:
[0092] a. Heating stage:
[0093] ①Within 0.5 hours, the temperature rises from room temperature to 80℃.
[0094] ②Raise the temperature from 80℃ to 120℃, increasing the temperature by 10℃ per hour.
[0095] b. Constant temperature stage
[0096] ③Keep constant temperature at 120℃ for 2 hours.
[0097] c. Cooling stage
[0098] ④ Cool down from 120℃ to 80℃, cooling down by 5℃ per hour.
[0099] ⑤Within 0.5 hours, reduce the temperature from 80℃ to room temperature.
[0100] g. Reference Figure 7 After curing, take out the layered material from the mold and check to make sure there are no obvious scratches on the surface of the layered material, no bubbles inside, and the interface between the layers is flat. Process the material into the required shape and size. Make sure there are no obvious defects in the processed specimen, then immerse the specimen in silicone oil and put it in an oven for annealing to eliminate the residual stress inside the layered material. The annealing temperature curve is as follows: Figure 8 As shown, the temperature of the layered material annealing setting is:
[0101] a. Heating stage:
[0102] ①Within 4 hours, the temperature is raised from room temperature to 150℃.
[0103] b. Constant temperature stage
[0104] ②Keep constant temperature at 150℃ for 5 hours.
[0105] c. Cooling stage
[0106] ③ Cool down from 150℃ to 120℃, cooling by 1℃ per hour.
[0107] ④ Cool down from 120℃ to room temperature, cooling down by 5℃ per hour.
[0108] Although the specific embodiments of the present invention have been described in conjunction with the accompanying drawings, it should be appreciated that the above description should not be considered as limiting the present invention. After reading the above content, various modifications and substitutions of the present invention will be obvious to those skilled in the art. Therefore, the protection scope of the present invention shall be defined by the attached claims, and any changes based on the claims of the present invention shall fall within the protection scope of the present invention.
Claims
1. A method for preparing a layered material for dynamic photoelasticity experiment, characterized in that: The following steps are involved: a. Measure the mechanical parameters of each layer of rock constituting the layered rock mass, and obtain various physical and mechanical parameters of each layer of rock constituting the layered rock mass; b. According to the measured physical and mechanical parameters of each layer of rock, determine the raw material ratio of the mixed solution corresponding to each layer; the raw materials for the mixed solution include epoxy resin, methyl hexahydrophthalic anhydride, accelerator DMP-30, epoxy resin defoamer, and plasticizer dibutyl phthalate; the epoxy resin standard specimens made from mixed solutions with different ratios are subjected to uniaxial compression test, shear test, splitting test and strain gauge electrical test to explore the variation law of material mechanical parameters of epoxy resin materials made from mixed solutions with different ratios; according to the similarity principle of model experiments, determine the ratio value of the epoxy resin material mixed solution corresponding to the mechanical parameters of each layer of rock material in the actual layered rock mass, in preparation for the later casting of layered epoxy resin photoelastic material; prepare each layer of mixed solution in turn according to the determined raw material ratio of the mixed solution, and stir fully under 80℃ water bath conditions; The first layer of mixed solution ratio is epoxy resin E-54: methyl hexahydrophthalic anhydride: plasticizer dibutyl phthalate: accelerator DMP-30: epoxy resin defoamer = 250:165:0:3:1; The second layer of mixed solution ratio is epoxy resin E-44: methyl hexahydrophthalic anhydride: plasticizer dibutyl phthalate: accelerator DMP-30: epoxy resin defoamer = 250:184:22:3:1; The ratio of the third layer of mixed solution is epoxy resin E-51: methyl hexahydrophthalic anhydride: plasticizer dibutyl phthalate: accelerator DMP-30: epoxy resin defoamer = 250:162:14:3:1; The ratio of the fourth layer mixed solution is epoxy resin E-44: methyl hexahydrophthalic anhydride: plasticizer dibutyl phthalate: accelerator DMP-30: epoxy resin defoamer = 250: 173: 34: 3: 1; The proportion of the fifth layer of mixed solution is epoxy resin E-51: methyl hexahydrophthalic anhydride: plasticizer dibutyl phthalate: accelerator DMP-30: epoxy resin defoamer = 250: 200: 38: 3: 1; The ratio of the sixth layer mixed solution is epoxy resin E-54: methyl hexahydrophthalic anhydride: plasticizer dibutyl phthalate: accelerator DMP-30: epoxy resin defoamer = 250:205:0:3:1; c. Pour the first layer of mixed solution into the mold and perform preliminary curing at a constant temperature; the preliminary curing temperature is 80°C and the temperature is kept constant for 2 hours; d. After the initial curing, install a fixture outside the mold, pour the second layer of mixed solution into the mold, and perform initial curing at a constant temperature; the initial curing temperature is 80°C, and the temperature is kept constant for 2 hours; e. Repeat steps c and d until each layer of the mixed solution is poured; f. After the pouring is completed, the layered epoxy resin material is heated and cured; g. After curing, the layered epoxy resin material is annealed.
2. The method for preparing a layered material for dynamic photoelastic experiment according to claim 1, characterized in that: In the step a, mechanical parameters of rock materials of each layer of layered rock are obtained by measuring mechanical parameters of standard specimens of each rock layer, including uniaxial compression test, shear test, splitting test and strain gauge electrical test, including elastic modulus, compressive strength, tensile strength, Poisson's ratio, internal friction angle and cohesion.
3. The method for preparing a layered material for dynamic photoelastic experiment according to claim 1, characterized in that: In the step b, firstly, a first layer of mixed solution is prepared according to a determined ratio, various raw materials required are weighed according to the raw material ratio, epoxy resin is first poured into a beaker, and then methyl hexahydrophthalic anhydride, plasticizer dibutyl phthalate, accelerator DMP-30, and epoxy resin defoamer are added in sequence, and the mixed solution is stirred under 80° C. water bath conditions; the stirring rate is 80-100 r / min; manual stirring is performed until the solution floating on the surface is evenly mixed with the lower layer, and then stirring is continued for 30 minutes under 80° C. water bath conditions with a water bath thermostatic stirrer; the entire stirring process is completed under closed conditions, and the room temperature is not lower than 25° C. During the stirring process, the water vapor generated by water bath heating on the stirring rod should be wiped off in time to prevent the water vapor from dripping into the mixed solution.
4. The method for preparing a layered material for dynamic photoelastic experiment according to claim 1, characterized in that: In the step c, the mold is made of double-layer tempered glass, and the inner surface of the double-layer tempered glass is evenly sprayed with epoxy resin release agent LP-1309. The double-layer tempered glass is separated by a seal and glued to the left and right lower edges of the glass with special glue to keep the distance between the double-layer glass the same. After gluing the seal and the tempered glass, they are clamped with a large clip, left at room temperature for 48 hours or baked in an oven at 80°C for 4 hours until they are completely set and hardened, and then the large clip on the mold is removed.
5. The method for preparing a layered material for dynamic photoelastic experiment according to claim 1, characterized in that: In the step c, the stirred first layer of mixed solution is quickly poured along the inner wall of the mold, so that the mixed solution flows down in strands, avoiding bubbles generated during the pouring of the mixed solution and affecting the subsequent experimental results; during the pouring process, the mold can be placed horizontally or tilted at a certain angle; the entire pouring process is guaranteed to be completed within 2 minutes, avoiding the pouring time being too long, which leads to a decrease in the temperature of the mixed solution, resulting in a decrease in its fluidity, and causing the upper liquid surface of the mixed solution in the mold to be uneven.
6. The method for preparing a layered material for dynamic photoelastic experiment according to claim 1, characterized in that: In the step d, the first layer of the mixed solution is initially cured at a constant temperature for 2 hours, at which time it solidifies into a jelly-like state and has no fluidity; the mold is taken out of the oven, 5-6 clamps are clamped on the bottom side of the mold, the clamp spacing is kept equal, the upper fulcrum of the clamp is just at the liquid surface, and the handle of the clamping screw of the clamp is rotated clockwise until it cannot rotate; the entire clamp installation process should be completed within 5 minutes, and after the installation is completed, the entire mold is immediately placed in a preheated 80°C oven.
7. The method for preparing a layered material for dynamic photoelastic experiment according to claim 1, characterized in that: In the step d, a second layer of mixed solution is prepared according to the determined raw material ratio of the mixed solution, and the preparation steps are the same as those of the first layer of mixed solution; the second layer of mixed solution begins to be stirred 30 minutes before the first layer of mixed solution is initially cured at a constant temperature, so as to ensure that the second layer of mixed solution has been stirred when the fixture is installed after the initial curing of the first layer of mixed solution.
8. A layered material for dynamic photoelasticity experiment obtained according to the preparation method according to any one of claims 1 to 7.
Citation Information
Patent Citations
Epoxy resin photoelastic model and manufacturing method thereof
CN105291326A
Production method of epoxy resin board for photo-elastic experimental test
CN106928657A